2015
DOI: 10.1093/cid/civ048
|View full text |Cite
|
Sign up to set email alerts
|

Colistin-Resistant Acinetobacter baumannii: Beyond Carbapenem Resistance

Abstract: Colistin-resistant A. baumannii occurred almost exclusively among patients who had received CMS for treatment of carbapenem-resistant, colistin-susceptible A. baumannii infection. Lipid A modification by the addition of phosphoethanolamine accounted for colistin resistance. Susceptibility testing for colistin should be considered for A. baumannii identified from CMS-experienced patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
290
3
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(310 citation statements)
references
References 36 publications
9
290
3
8
Order By: Relevance
“…While the number of reports on colistin resistance have gradually been increasing in other countries (14) and a report based on a study conducted in the United States showed that 5.3% of all Acinetobacter strains detected during an eight-year period were resistant to colistin (15,16), encounters with colistin-resistant Acinetobacter species are still rare in Japan. The production and sale of colistin in Japan was only approved in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…While the number of reports on colistin resistance have gradually been increasing in other countries (14) and a report based on a study conducted in the United States showed that 5.3% of all Acinetobacter strains detected during an eight-year period were resistant to colistin (15,16), encounters with colistin-resistant Acinetobacter species are still rare in Japan. The production and sale of colistin in Japan was only approved in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases polymyxins are the only therapeutic solution. Unfortunately, the isolation of colistin-resistant carbapenem-resistant A. baumannii is on the rise [27] . A large spectrum of nosocomial infections are caused by A. baumannii including bloodstream infections, pneumonia, catheter-associated infections, etc.…”
Section: Acinetobacter Baumanniimentioning
confidence: 99%
“…Qureshi ZA et al found that all 19 patients initially infected with colistin-susceptible A. baumannii received therapy with intravenous CMS, inhaled CMS, or both, prior to isolation of colistin-resistant A. baumannii and the median interval between the isolation of the colistinsusceptible A. baumannii isolate and the colistin-resistant A. baumannii isolate was 20 days (range, 4-99). They also observed an all-cause mortality of 30% (6/20) at 30 days (45).…”
Section: Combination Therapymentioning
confidence: 89%